Project Report on Strategic Business Intelligency in Banking - AMAR R GAJARE (2006)
INTERNAL GUIDE:SHANTAKUMAR B PATIL,MVJCE EXTERNAL GUIDE:HANEEF NAWAZ, ANTHESIS TECHNOLOGIES
Keywords: Strategic Business Intelligency in Banking